2009
DOI: 10.1124/jpet.109.158352
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-2 Deletion Causes Endothelial Cell Activation Marked by Oxidative Stress, Inflammation, and Angiogenesis

Abstract: In previous studies, we have shown that heme oxygenase (HO)-2 null [HO-2(Ϫ/Ϫ)] mice exhibit a faulty response to injury; chronic inflammation and massive neovascularization replaced resolution of inflammation and tissue repair. Endothelial cells play an active and essential role in the control of inflammation and the process of angiogenesis. We examined whether HO-2 deletion affects endothelial cell function. Under basal conditions, HO-2(Ϫ/Ϫ) aortic endothelial cells (mAEC) showed a 3-fold higher expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 34 publications
7
55
0
Order By: Relevance
“…For example, although the heme oxygenase-2 knockout mouse is characterized by selective vascular inflammation and heightened oxidative stress, blood pressure is not elevated. 33,34 The DOCA-salt model of hypertension has been widely used to investigate the pathogenesis and reversibility of left ventricular hypertrophy and myocardial fibrosis, 35,36 and in the present study we showed that CXCR4 antagonism significantly abrogated the effect of DOCA on left ventricular mass and myocardial fibrosis. Our findings in this regard are limited by the absence of a control …”
Section: Discussionsupporting
confidence: 59%
“…For example, although the heme oxygenase-2 knockout mouse is characterized by selective vascular inflammation and heightened oxidative stress, blood pressure is not elevated. 33,34 The DOCA-salt model of hypertension has been widely used to investigate the pathogenesis and reversibility of left ventricular hypertrophy and myocardial fibrosis, 35,36 and in the present study we showed that CXCR4 antagonism significantly abrogated the effect of DOCA on left ventricular mass and myocardial fibrosis. Our findings in this regard are limited by the absence of a control …”
Section: Discussionsupporting
confidence: 59%
“…HO-2 is thus believed to contribute to normal housekeeping. And it has been reported that HO-2 behaves as a basal tone of anti-inflammatory signals, and deletion of HO-2 disables execution of the acute inflammatory and reparative response, leading to an exaggerated inflammatory response including increased oxidative stress and angiogenesis (Seta et al, 2006;Bellner et al, 2009). Moreover, it is known that HO-2 is induced by the treatment of corticosteroids (Maines et al, 1996), which is an important protective response during acute illness or stress, and is widely used as a treatment of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice deficient in HO-2 have revealed several important functions of this enzyme. For example, HO-2 deletion causes EC activation marked by oxidative stress, inflammation, and angiogenesis (23), which underscores the importance of HO-2 in the regulation of EC homeostasis. HO-2 deficiency disables execution of the acute inflammatory and reparative response after epithelial injury and leads to an exaggerated inflammatory response in antigen-induced peritonitis (231), implicating a role for HO-2 in the regulation of the inflammatory and reparative response to injury.…”
Section: B Heme Oxygenase-2mentioning
confidence: 99%